Motivation, expectations and the gender pay gap for UK graduates - Arnaud Chevalier (University College Dublin, Department of Economics, 2004)
Focussing on recent UK graduates, a wage gap of 12% is found. The unexplained component of the gap is small and a large fraction of the gap can be explained by subject choice, job characteristics, motivation and expectation variables. Motivation and expectations account for 44% of the explained gap, thus most studies over-estimate the unexplained component of the gender wage gap. Following stereotypes, women tend to be more altruistic and less career oriented than men, character traits that are less rewarded by employers. The principal component of the gender wage gap is expectations about childrearing. These conservative attitudes affect women's wages even at an early stage of their career. Without a change in attitude, the gender wage gap is likely to remain.
hdl:10197/1310
Keywords: J16; J13; J29; J70; 330; gender wage gap; attitude